CHILDREN’S CHARACTER - Narzullayeva, Muhayyo Iftixor qizi (INTERNATIONAL CONFERENCES, 2022)
There are too many children here who are affected by family situations. The family ensures that the child becomes self-confident and responsible. Children have many opportunities to speak. A child's pursuit of life is very interesting. There are shows on TV that are harmful to children.